Perceived Physical Competence, Self-Esteem, and Leadership among Girls: A Program Evaluation of GOALS (Girls Organizing and Learning Sport) - Bailey Csabai; Barbara A. Pollard; Sarah J. Woodruff (MDPI AG, 2024)
This study evaluated a leadership-based physical activity program, Girls Organizing and Learning Sport (GOALS), by assessing changes in health behaviours, physical competence, self-esteem, and leadership. Of the 466 participants who enrolled in the program, 102 (22%) completed a pre-and post-program survey containing questions concerning demographics, physical activity, physical competence, self-esteem, and leadership. The GOALS program was held twice (fall 2022/winter 2023) and consisted of two-hour weekly sessions over four weeks at nine different locations. Paired-sample t-tests, Chi-squares, and one-way ANOVA tests were utilized to analyze differences before and after the GOALS program. Results revealed that more participants were involved in school sports, community sports, and regular physical activity post-program (all p's < 0.05). A significant difference was also observed between pre-and post-test scores for physical competence and self-esteem (p's < 0.05). However, the program did not elicit changes in health behaviours or total leadership scores (all p's > 0.05). Moreover, significant results were observed between physical competence difference scores and those who care for their health by exercising (p = 0.025), leadership difference scores and those who take care of their health by exercising (p = 0.044), self-esteem difference scores by program location (p = 0.001), and physical competence difference scores by ethnicity (p = 0.003). Overall, further research into the design, administration, and targeted outcomes is recommended for future sessions.